Новая находка Thompsodinium intermedium (R.H. Thomps.) Bourr. (Dinophyta) в Украине - Крахмальный, А.Ф. (Альгология, 2011)
Найден редкий вид динофитовых водорослей Thompsodinium intermedium в планктоне оз. Бучак (июль 2009 г., Каневский р-н, Черкасская обл., Украина). Это второе упоминание вида для водоемов Украины. Впервые в Украине вид был обнаружен в 1966 г. в оз. Белом (Харьковская обл., окрестности биостанции Харьковского го с. ун-та). Упоминался для пресных водоемов США, Белиза (бывший Британский Гондурас) и Кубы. Приведены рисунки, описание, распространение, сравнение с морфологически близкими видами, уточнено систематическое положение вида (переведен из сем. Gonyaulacaceae в сем. Peridiniaceae). Предложена новая видовая комбинация Thompsodinium pseudo-intermedium (Couté et A. Iltis) Krachm. comb. nov. A rare species of Thompsodinium intermedium (Dinophyta) was found in the plankton of Buchak Lake (July 2009, Kanev district, Cherkasy region, Ukraine). It is the second reference of this species for reservoirs of Ukraine. For the first time the species was registered in 1966 in Lake White (Kharkiv region, near the biological station of Kharkov State University). Thompsodinium intermedium was referred to freshwater reservoirs of the USA, Belize (formerly British Honduras) and Cuba. Figures, description, distribution, comparison with morphologically similar species are given. Systematic position of studied species (it has been transferred from the family Gonyaulacaceae to the family Peridiniaceae) was clarified. A new species combination of Thompsodinium pseudo -intermedium (Couté et Iltis) Krachm. comb. nov. was proposed.